The Double Burden of Malnutrition in East Asia and the Pacific : Evidence and Lessons for a Multisectoral Response - Shrimpton, Roger (World Bank, Washington, DC, 2017)
Global trends indicate that overlapping burdens of undernutrition and overnutrition—the double burden of malnutrition (DBM)—are the new normal (IFPRI 2014); indeed, most East Asia and Pacific (EAP) countries now have a DBM problem. This report explores the nature of nutrition problems affecting EAP countries to understand the sectoral and system-wide actions necessary for a coordinated approach to improving nutrition. The report (i) synthesizes evidence related to the burden of malnutrition in EAP, (ii) identifies the rationale for a multisectoral approach to DBM practitioners working across sectors in EAP, and (iii) provides an overview of the types of actions and interventions needed to address the DBM in a coordinated fashion across the life course. Actions across health and nonhealth sectors—ranging from implementation of national-level policy measures and complemented by interventions at the community and individual levels to support behavior change—are needed to prevent escalation of overweight and obesity. Among sectoral priority actions, the health sector plays an important role in monitoring health and nutrition outcomes, preventing and treating infectious and noncommunicable diseases associated with malnutrition, and providing interventions that affect individuals’ nutrient intakes. Similarly, nonhealth sectors have expertise and resources to deliver interventions related to the underlying causes of malnutrition. Further, systems-strengthening efforts are needed to support an environment that addresses the DBM across the life course, including increasing DBM-sensitivity of policy frameworks; leadership, coordination, and accountability; workforce capacity; and knowledge and evidence. Reducing the DBM is fundamental to sustainable development in EAP. EAP countries must shift from dichotomized policies addressing either undernutrition or overnutrition and develop coherent frameworks to address malnutrition in all forms for all life stages. Integrated preventive and curative interventions for undernutrition and overnutrition—implemented across the life course by multiple sectors—can forestall massive economic and human development consequences for future generations.